Cost savings associated with extended battery longevity in cardiac resynchronization therapy defibrillators - Jeffrey L. Williams, MD, MS, FACC, FHRS; Ryoko Sato, PhD; Caroline M. Jacobsen, MPhil (Heart Rhythm O2, 2024)
Background: Cardiac resynchronization therapy-defibrillators (CRT-D) are devices established as treatment for symptomatic heart failure patients at risk of sudden cardiac death. Battery depletion poses a significant clinical and economic burden; extended service life may reduce costs because of generator changes and associated complications. Objective: This study estimated cost-savings associated with extended battery longevity in Medicare patients receiving CRT-D implantation. Methods: A decision tree was used to explore 3 battery capacities: 1.0 ampere-hours (Ah), 1.6Ah, and 2.1Ah. Yearly risk of all-cause mortality, device-related complications, and end of battery life were estimated. Over 6 years, estimated costs included device implantation, replacement, follow-up appointments, and complications. Results: The average total costs to Medicare over 6 years were $41,527, $48,515, and $56,647 per person (USD 2023) for the 2.1 Ah, 1.6 Ah, and 1.0 Ah, respectively. The total per-person replacement cost for the 1.0-Ah devices was more than 4 times that of the 2.1-Ah devices ($20,126 vs $5,006). When extrapolated to the total number of CRT-D implants over a 6-year period, the difference in costs between 2.1-Ah and 1.0-Ah battery capacity exceeded $500 million. Conclusion: Extended longevity CRT-D batteries demonstrate significant cost savings to Medicare over 6 years. These data indicate long-term economic considerations should be included in device selection.